P188 Prevalence of Serum Eosinophilia at time of admission with an Exacerbation of COPD. (14th November 2013) - Halpin, DMG
Abstract : COPD is generally viewed as a disease driven by neutrophillic inflammation but up to 40% of COPD patients have an inflammatory pattern that includes elevated eosinophils (Saha, 2006) and there has been recent interest in the role of eosinophils in the aetiology and pathophysiology of exacerbations of COPD. Increased eosinophilic airway inflammation has been reported during exacerbations of COPD and peripheral eosinophils levels have been used as a surrogate to predict response to corticosteroid therapy. Treatment strategies with oral and inhaled steroids to reduce sputum eosinophils in COPD reduce exacerbation rates compared to a conventional care and there has been interest in using anti-eosinophil therapy to modify the clinical course of exacerbations. Data were collected on 66 patients admitted with an acute exacerbation of COPD between Nov 2011 and Feb 2012 as part of an assessment of a discharge bundle. The mean age of the patients was 72 (range 49–91) and mean FEV1 33% predicted. Serum eosinophils were measured routinely in full blood counts performed at the time of admission. 20 patients (30%) had no detectable eosinophils, and 6 (9%) had raised eosinophil counts (normal range 0.04–0.40 x 10^9/l). The median eosinophil count was 0.07. One patient had an eosinophil count of 15.24 on admission, having previously had intermittently mildly elevated counts (up to 1.57) since at least 2000. Excluding this patient, the mean (SE) eosinophil count was 0.37 (0.23). The distribution of serum eosinophil counts is shown in fig 1 . In this group of patients, serum eosinophilia (>0.4) was seen in only 9% of patients at the time of admission. This may have been affected by prior self management with oral steroids. References: Saha S, Brightling CE. Int J Chron Obstruct Pulmon Dis . 2006;1(1):39–47.